Precalculus

Trigonometry

Trig Identities Logo

Addition and Subtraction Formulas for Sine and Cosine

Cosine Subtraction Formula

Let \(\alpha, \beta\) be two angles such that \(\alpha \gt \beta.\) Take the following points on a unit circle: \(A\left( 0 \right),\) \(M\left( \alpha \right),\) \(N\left( \beta \right),\) \(P\left( {\alpha – \beta } \right).\)

Deriving the difference formula for cosine
Figure 1.

The coordinates of these points are

\[{A = A\left( {1,0} \right),\;\;}\kern0pt{M = M\left( {\cos \alpha ,\sin \alpha } \right),\;\;}\kern0pt{N = N\left( {\cos \beta ,\sin \beta } \right),\;\;}\kern0pt{P = P\left( {\cos \left( {\alpha – \beta } \right),\sin \left( {\alpha – \beta } \right)} \right).}\]

Since \(\angle MON = \angle POA = \alpha – \beta,\) the line segments \(\color{#cc00ff}{MN}\) and \(\color{#0099ff}{AP}\) have the same length:

\[\left| \color{#cc00ff}{MN} \right| = \left| \color{#0099ff}{AP} \right|.\]

The distance between two points on a plane is given by the formula

\[d = \sqrt {{{\left( {{x_1} – {x_2}} \right)}^2} + {{\left( {{y_1} – {y_2}} \right)}^2}} .\]

Therefore,

\[{{\left| \color{#cc00ff}{MN} \right|^2} }={ {\left( {{x_M} – {x_N}} \right)^2} + {\left( {{y_M} – {y_N}} \right)^2} }={ {\left( {\cos \alpha – \cos \beta } \right)^2} + {\left( {\sin \alpha – \sin \beta } \right)^2} }={ {\cos ^2}\alpha – 2\cos \alpha \cos \beta + {\cos ^2}\beta }+{ {\sin ^2}\alpha – 2\sin \alpha \sin \beta + {\sin ^2}\beta }={ \underbrace {{{\cos }^2}\alpha + {{\sin }^2}\alpha }_1 + \underbrace {{{\cos }^2}\beta + {{\sin }^2}\beta }_1 }-{ 2\left( {\cos \alpha \cos \beta }+{ \sin \alpha \sin \beta } \right) }={ 2 – 2\left( {\cos \alpha \cos \beta + \sin \alpha \sin \beta } \right);}\]

Similarly we find the distance \(\left| \color{#0099ff}{AP} \right|\) squared:

\[{{\left| \color{#0099ff}{AP} \right|^2} }={ {\left( {{x_A} – {x_P}} \right)^2} + {\left( {{y_A} – {y_P}} \right)^2} }={ {\left( {1 – \cos \left( {\alpha – \beta } \right)} \right)^2} }+{ {\left( {0 – \sin \left( {\alpha – \beta } \right)} \right)^2} }={ 1 – 2\cos \left( {\alpha – \beta } \right) }+{ \underbrace {{{\cos }^2}\left( {\alpha – \beta } \right) + {{\sin }^2}\left( {\alpha – \beta } \right)}_1 }={ 2 – 2\cos \left( {\alpha – \beta } \right).}\]

The cosine subtraction formula follows from the equality \({\left| \color{#cc00ff}{MN} \right|^2} = {\left| \color{#0099ff}{AP} \right|^2}:\)

Cosine subtraction formula

Cosine Addition Formula

Consider two points \(N\left( \beta \right)\) and \(L\left( { – \beta } \right)\) lying on the terminal sides of the angles \(\beta\) and \(-\beta,\) respectively.

Sine is odd, cosine is even.
Figure 2.

These points are symmetric with respect to the \(x-\)axis. Therefore, they have the same \(x-\)coordinates. Their \(y-\)coordinates are equal in magnitude but opposite in sign. In other words, the cosine function is even and the sine function is odd:

Cosine and sine of a negative angle.

Now, let’s go back to the cosine subtraction formula and replace \(\beta \to -\beta:\)

\[{\cos \left( {\alpha + \beta } \right) }={ \cos \alpha \cos \left( { – \beta } \right) }+{ \sin \alpha \sin \left( { – \beta } \right).}\]

Since cosine is even and sine is odd, we get the cosine addition identity in the form

Cosine addition formula

Special Cases

Substitute \(\alpha = \large{\frac{\pi }{2}}\normalsize\) in the cosine subtraction formula:

\[{\cos \left( {\frac{\pi }{2} – \beta } \right) }={ \cos \frac{\pi }{2}\cos \beta }+{ \sin \frac{\pi }{2}\sin \beta }={ 0 \cdot \cos \beta }+{ 1 \cdot \sin \beta }={ \sin \beta ,}\]

that is,

Cofunction identity cos(pi/2-beta)=sin(beta)

Replace \(\beta \to \large{\frac{\pi }{2}}\normalsize – \beta\) in the last expression:

\[{\sin \left( {\frac{\pi }{2} – \beta } \right) }={ \cos \left( {\frac{\pi }{2} – \left( {\frac{\pi }{2} – \beta } \right)} \right) }={ \cos \beta ,}\]

or

Cofunction identity sin(pi/2-beta)=cos(beta)

Similarly, take the cosine addition formula and substitute \(\alpha = \large{\frac{\pi }{2}}\normalsize:\)

\[{\cos \left( {\frac{\pi }{2} + \beta } \right) }={ \cos \frac{\pi }{2}\cos \beta – \sin \frac{\pi }{2}\sin \beta }={ 0 \cdot \cos \beta – 1 \cdot \sin \beta }={ – \sin \beta .}\]

We got the following identity:

Trig identity cos(pi/2+beta)=-sin(beta)

By changing \(\beta \to -\beta\) in the identity \(\sin \left( {\large{\frac{\pi }{2}}\normalsize – \beta } \right) = \cos \beta ,\) we obtain

\[{\sin \left( {\frac{\pi }{2} + \beta } \right) }={ \cos \left( { – \beta } \right) }={ \cos \beta ,}\]

that is,

Trig identity sin(pi/2+beta) = cos(beta)

Sine Subtraction Formula

Using cofunction identities from the previous section, we derive the sine subtraction formula:

\[{\sin \left( {\alpha – \beta } \right) }={ \cos \left( {\frac{\pi }{2} – \left( {\alpha – \beta } \right)} \right) }={ \cos \left( {\left( {\frac{\pi }{2} – \alpha } \right) + \beta } \right) }={ \cos \left( {\frac{\pi }{2} – \alpha } \right)\cos \beta }-{ \sin \left( {\frac{\pi }{2} – \alpha } \right)\sin \beta }={ \sin \alpha \cos \beta – \cos \alpha \sin \beta .}\]

Thus, we have

Sine subtraction formula

Sine Addition Formula

If we replace \(\beta \to -\beta\) in this formula, we get the sine addition identity:

\[{\sin \left( {\alpha + \beta } \right) }={ \sin \alpha \cos \left( { – \beta } \right) }-{ \cos \alpha \sin \left( { – \beta } \right) }={ \sin \alpha \cos \beta + \cos \alpha \sin \beta .}\]

Hence,

Sine addition formula

Solved Problems

Click or tap a problem to see the solution.

Example 1

Calculate \(\cos \large{\frac{{5\pi }}{{12}}}\normalsize.\)

Example 2

Calculate \(\sin \large{\frac{{\pi }}{{12}}}\normalsize.\)

Example 3

Find the exact value of \(\sin \large{\frac{{7\pi }}{{5}}}\normalsize.\)

Example 4

Find the exact value of \(\cos 105^\circ.\)

Example 5

Determine the value of \(\cos \left( {\large{\frac{\pi }{3}}\normalsize + \alpha } \right)\) if \(\sin \alpha = \large{\frac{1}{{\sqrt 3 }}}\normalsize\) and the angle \(\alpha\) lies in the \(1\text{st}\) quadrant.

Example 6

Determine the value of \(\sin \left( {\large{\frac{\pi }{4}}\normalsize – \beta } \right)\) if \(\cos \beta = -\large{\frac{1}{2}}\normalsize\) and the angle \(\beta\) is in the \(2\text{nd}\) quadrant.

Example 7

Prove the identity \[{\cos \left( {\alpha + \beta } \right)\cos \left( {\alpha – \beta } \right) }={ {\cos ^2}\alpha – {\sin ^2}\beta. }\]

Example 8

Prove the identity \[{\sin \left( {\alpha + \beta } \right)\sin \left( {\alpha – \beta } \right) }={ {\sin ^2}\alpha – {\sin ^2}\beta.}\]

Example 9

Find the greatest and least value of \(\sin\alpha + \cos\alpha.\)

Example 10

Find the greatest and least value of \(\sin\beta – \sqrt{3}\cos\beta.\)

Example 1.

Calculate \(\cos \large{\frac{{5\pi }}{{12}}}\normalsize.\)

Solution.

We represent the angle \(\large{\frac{{5\pi }}{{12}}}\normalsize\) as the sum of two angles:

\[{\frac{{5\pi }}{{12}} = \frac{{3\pi + 2\pi }}{{12}} }={ \frac{{3\pi }}{{12}} + \frac{{2\pi }}{{12}} }={ \frac{\pi }{4} + \frac{\pi }{6}.}\]

Using the cosine addition formula, we have

\[{\cos \frac{{5\pi }}{{12}} }={ \cos \left( {\frac{\pi }{4} + \frac{\pi }{6}} \right) }={ \cos \frac{\pi }{4}\cos \frac{\pi }{6} – \sin \frac{\pi }{4}\sin \frac{\pi }{6} }={ \frac{{\sqrt 2 }}{2} \cdot \frac{{\sqrt 3 }}{2} – \frac{{\sqrt 2 }}{2} \cdot \frac{1}{2} }={ \frac{{\sqrt 6 }}{4} – \frac{{\sqrt 2 }}{4} }={ \frac{{\sqrt 6 – \sqrt 2 }}{4}.}\]

Example 2.

Calculate \(\sin \large{\frac{{\pi }}{{12}}}\normalsize.\)

Solution.

Since

\[{\frac{\pi }{{12}} = \frac{{4\pi – 3\pi }}{{12}} }={ \frac{{4\pi }}{{12}} – \frac{{3\pi }}{{12}} }={ \frac{\pi }{3} – \frac{\pi }{4},}\]

then by the sine subtraction formula:

\[{\sin \frac{\pi }{{12}} }={ \sin \left( {\frac{\pi }{3} – \frac{\pi }{4}} \right) }={ \sin \frac{\pi }{3}\cos \frac{\pi }{4} – \cos \frac{\pi }{3}\sin \frac{\pi }{4} }={ \frac{{\sqrt 3 }}{2} \cdot \frac{{\sqrt 2 }}{2} – \frac{1}{2} \cdot \frac{{\sqrt 2 }}{2} }={ \frac{{\sqrt 6 }}{4} – \frac{{\sqrt 2 }}{4} }={ \frac{{\sqrt 6 – \sqrt 2 }}{4}.}\]

Notice that

\[{\sin \frac{\pi }{{12}} }={ \cos \left( {\frac{\pi }{2} – \frac{\pi }{{12}}} \right) }={ \cos \frac{{6\pi – \pi }}{{12}} }={ \cos \frac{{5\pi }}{{12}} }={ \frac{{\sqrt 6 – \sqrt 2 }}{4}.}\]

Example 3.

Find the exact value of \(\sin \large{\frac{{7\pi }}{{5}}}\normalsize.\)

Solution.

We write the given angle in the form

\[{\frac{{7\pi }}{{12}} = \frac{{4\pi + 3\pi }}{{12}} }={ \frac{{4\pi }}{{12}} + \frac{{3\pi }}{{12}} }={\frac{\pi }{3} + \frac{\pi }{4}.}\]

Use the sine addition identity:

\[{\sin \frac{{7\pi }}{{12}} }={ \sin \left( {\frac{\pi }{3} + \frac{\pi }{4}} \right) }={ \sin \frac{\pi }{3}\cos \frac{\pi }{4} + \cos \frac{\pi }{3}\sin \frac{\pi }{4} }={ \frac{{\sqrt 3 }}{2} \cdot \frac{{\sqrt 2 }}{2} + \frac{1}{2} \cdot \frac{{\sqrt 2 }}{2} }={ \frac{{\sqrt 6 }}{4} + \frac{{\sqrt 2 }}{4} }={ \frac{{\sqrt 6 + \sqrt 2 }}{4}.}\]

Example 4.

Find the exact value of \(\cos 105^\circ.\)

Solution.

We write the angle \(105^\circ\) as the sum of two angles:

\[{105^\circ} = {60^\circ} + {45^\circ}.\]

Therefore,

\[{\cos {105^\circ} = \cos \left( {{{60}^\circ} + {{45}^\circ}} \right) }={ \cos {60^\circ}\cos {45^\circ} – \sin {60^\circ}\sin {45^\circ} }={ \frac{1}{2} \cdot \frac{{\sqrt 2 }}{2} – \frac{{\sqrt 3 }}{2} \cdot \frac{{\sqrt 2 }}{2} }={ \frac{{\sqrt 2 – \sqrt 6 }}{4} }={ – \frac{{\sqrt 6 – \sqrt 2 }}{4}.}\]

Example 5.

Determine the value of \(\cos \left( {\large{\frac{\pi }{3}}\normalsize + \alpha } \right)\) if \(\sin \alpha = \large{\frac{1}{{\sqrt 3 }}}\normalsize\) and the angle \(\alpha\) lies in the \(1\text{st}\) quadrant.

Solution.

The cosine function is positive in the \(1\text{st}\) quadrant. Therefore

\[{\cos \alpha = \sqrt {1 – {{\sin }^2}\alpha } }={ \sqrt {1 – {{\left( {\frac{1}{{\sqrt 3 }}} \right)}^2}} }={ \sqrt {1 – \frac{1}{3}} }={ \sqrt {\frac{2}{3}} }={ \frac{{\sqrt 2 }}{{\sqrt 3 }}.}\]

Now we use the cosine addition formula:

\[{\cos \left( {\frac{\pi }{3} + \alpha } \right) }={ \cos \frac{\pi }{3}\cos \alpha – \sin \frac{\pi }{3}\sin \alpha }={ \frac{1}{2} \cdot \frac{{\sqrt 2 }}{{\sqrt 3 }} – \frac{{\sqrt 3 }}{2} \cdot \frac{1}{{\sqrt 3 }} }={ \frac{{\sqrt 2 – \sqrt 3 }}{{2\sqrt 3 }} }={ \frac{{\sqrt 6 – 3}}{6}.}\]

We can note that the cosine of this angle is negative.

Example 6.

Determine the value of \(\sin \left( {\large{\frac{\pi }{4}}\normalsize – \beta } \right)\) if \(\cos \beta = -\large{\frac{1}{2}}\normalsize\) and the angle \(\beta\) is in the \(2\text{nd}\) quadrant.

Solution.

The sine is positive in the \(2\text{nd}\) quadrant. Hence,

\[{\sin \beta = \sqrt {1 – {{\sin }^2}\beta } }={ \sqrt {1 – {{\left( { – \frac{1}{2}} \right)}^2}} }={ \sqrt {1 – \frac{1}{4}} }={ \sqrt {\frac{3}{4}} }={ \frac{{\sqrt 3 }}{2}.}\]

Using the sine difference identity, we obtain

\[{\sin \left( {\frac{\pi }{4} – \beta } \right) }={ \sin \frac{\pi }{4}\cos \beta – \cos \frac{\pi }{4}\sin \beta }={ \frac{{\sqrt 2 }}{2} \cdot \left( { – \frac{1}{2}} \right) – \frac{{\sqrt 2 }}{2} \cdot \frac{{\sqrt 3 }}{2} }={ – \frac{{\sqrt 2 – \sqrt 6 }}{4} }={ \frac{{\sqrt 6 – \sqrt 2 }}{4}.}\]

Example 7.

Prove the identity \[{\cos \left( {\alpha + \beta } \right)\cos \left( {\alpha – \beta } \right) }={ {\cos ^2}\alpha – {\sin ^2}\beta.}\]

Solution.

Simplify the left-hand side \(LHS\) using the cosine addition and subtraction formulas:

\[{LHS }={ \cos \left( {\alpha + \beta } \right)\cos \left( {\alpha – \beta } \right) }={ \left( {\cos \alpha \cos \beta – \sin \alpha \sin \beta } \right)}\kern0pt{\cdot\left( {\cos \alpha \cos \beta + \sin \alpha \sin \beta } \right) }={ {\cos ^2}\alpha \,{\cos ^2}\beta – {\sin ^2}\alpha\,{\sin ^2}\beta .}\]

Recall that

\[{{\cos ^2}\beta = 1 – {\sin ^2}\beta \;\;\text{and}\;\;}\kern0pt{{\sin ^2}\alpha = 1 – {\cos ^2}\alpha .}\]

Then

\[\require{cancel}{LHS }={ {\cos ^2}\alpha \left( {1 – {{\sin }^2}\beta } \right) }-{ \left( {1 – {{\cos }^2}\alpha } \right){\sin ^2}\beta }={ {\cos ^2}\alpha – \cancel{{\cos ^2}\alpha \,{\sin ^2}\beta }}-{ {\sin ^2}\beta + \cancel{{\cos ^2}\alpha \,{\sin ^2}\beta} }={ {\cos ^2}\alpha – {\sin ^2}\beta }={ RHS.}\]

Example 8.

Prove the identity \[{\sin \left( {\alpha + \beta } \right)\sin \left( {\alpha – \beta } \right) }={ {\sin ^2}\alpha – {\sin ^2}\beta.}\]

Solution.

We write the left-hand side in the form

\[{LHS }={ \sin \left( {\alpha + \beta } \right)\sin \left( {\alpha – \beta } \right) }={ \left( {\sin \alpha \cos \beta + \cos \alpha \sin \beta } \right)}\kern0pt{\cdot\left( {\sin \alpha \cos \beta – \cos \alpha \sin \beta } \right) }={ {\sin ^2}\alpha\, {\cos ^2}\beta – {\cos ^2}\alpha \,{\sin ^2}\beta .}\]

Using the Pythagorean trig identities

\[{{\cos ^2}\alpha = 1 – {\sin ^2}\alpha ,\;\;}\kern0pt{{\cos ^2}\beta = 1 – {\sin ^2}\beta ,}\]

we get

\[{LHS }={ {\sin ^2}\alpha \left( {1 – {{\sin }^2}\beta } \right) }-{ \left( {1 – {{\sin }^2}\alpha } \right){\sin ^2}\beta }={ {\sin ^2}\alpha – \cancel{{\sin ^2}\alpha \,{\sin ^2}\beta} }-{ {\sin ^2}\beta + \cancel{{\sin ^2}\alpha \,{\sin ^2}\beta} }={ {\sin ^2}\alpha – {\sin ^2}\beta }={ RHS.}\]

Example 9.

Find the greatest and least value of \(\sin\alpha + \cos\alpha.\)

Solution.

We denote this expression by \(A.\) Using the auxiliary angle \(\frac{\pi }{4},\) we have

\[{\frac{{A\sqrt 2 }}{2} }={ \sin \alpha \frac{{\sqrt 2 }}{2} + \cos \alpha \frac{{\sqrt 2 }}{2} }={ \sin \alpha \cos \frac{\pi }{4} + \cos \alpha \sin \frac{\pi }{4} }={ \sin \left( {\alpha + \frac{\pi }{4}} \right).}\]

Hence,

\[A = \sqrt 2 \sin \left( {\alpha + \frac{\pi }{4}} \right).\]

The function \(\sin \left( {\alpha + \large{\frac{\pi }{4}}\normalsize} \right)\) ranges from \(-1\) to \(1.\) Therefore, the maximum value of \(A\) is \(\sqrt{2},\) and the minimum value is \(-\sqrt{2}.\)

Example 10.

Find the greatest and least value of \(\sin\beta – \sqrt{3}\cos\beta.\)

Solution.

Let the value of this expression be denoted by \(B.\) We can represent it in the following form:

\[{\frac{B}{2} }={ \frac{1}{2}\sin \beta – \frac{{\sqrt 3 }}{2}\cos \beta }={ \sin \frac{\pi }{6}\sin \beta – \cos \frac{\pi }{6}\cos \beta }={ – \left( {\cos \frac{\pi }{6}\cos \beta – \sin \frac{\pi }{6}\sin \beta } \right) }={ – \cos \left( {\frac{\pi }{6} + \beta } \right).}\]

Then

\[B = – 2\cos \left( {\frac{\pi }{6} + \beta } \right).\]

The maximum value of cosine is \(1,\) and the minimum value is \(-1.\) Respectively, the greatest value of \(B\) is \(2,\) and the least value is\(-2.\)